RANCANG BANGUN PROTOTYPE SISTEM KONTROL KECEPATAN MOTOR DC PADA SISTEM PENGADUKAN PROSES KOAGULASIDAN FLOKULASI DALAM PENGOLAHAN AIR BERSIH MENGGUNAKAN KONTROLER PID DIGITAL - Setyabudi, Nadya Sekarsari; Rusli, Moch.; Siswojo, Bambang (Jurnal Mahasiswa TEUB, 2024)
The coagulation and flocculation processes in water treatment systems are influenced by the appropriate mixing speed and time to ensure the uniform distribution of coagulants and flocculants and the optimal formation of flocs. Instability in the agitator motor speed can disrupt process efficiency and the quality of the treated water. Therefore, a DC motor speed control system using a PID (Proportional, Integral, Derivative) controller is designed to maintain stable motor rotation, especially when facing disturbances such as gravel. The system is designed to maintain motor speed according to the desired setpoint, with coagulation processes in the range of 403–670 RPM and flocculation processes in the range of 67 100 RPM. The first modified Ziegler-Nichols tuning method was used to determine the optimal PID control parameters, resulting in values of Kp = 78.6, Ki = 6.5, and Kd = 2. Additionally, an IR-Speed sensor is employed to detect motor rotation speed, which is then displayed via an LCD. Experimental results on raw water with a turbidity of 55 NTU demonstrated that the system could reach a steady state within 2 seconds. No overshoot was observed, and the system achieved a steady-state error (ESS) of 0.14% during slow mixing. The system met the desired performance criteria with a fast steady-state response and adhered to the specified design parameters. The system achieved a turbidity removal efficiency of 82.04%, indicating excellent performance in reducing turbidity and dissolved particles in the water. These findings confirm that the implemented control system effectively fulfills its intended purpose of producing water suitable for further treatment for daily use, although not for direct consumption as drinking water.Keywords: DC Motor, PID Controller, Coagulation, Flocculation